Transmission of Opisthorchis viverrini, Schistosoma mekongi and soil-transmitted helminthes on the Mekong Islands, Southern Lao PDR - Youthanavanh Vonghachack; Peter Odermatt; Keoka Taisayyavong; Souphanh Phounsavath; Kongsap Akkhavong; Somphou Sayasone (BMC, 2017)
Abstract Background Prevalence of Opisthorchis viverrini, Schistosoma mekongi and soil-transmitted helminths (STH) remains high in Lao People's Democratic Republic (Lao PDR), despite control efforts including mass-drug administration, education and communication campaigns. New approaches are required to advance helminth control. Methods An ecohealth study was conducted on two Mekong islands in Southern Laos. Demographic and behavioural data were collected by questionnaire. Human and animal reservoir stools were examined. Bithynia spp. and Neotricula aperta snails were examined using shedding. Fresh water fish were examined using digestion technique. Multivariate random-effects analysis was used to find risk factors associated with helminth infections. Results Human infection rates with O. viverrini, hookworm, S. mekongi, Trichuris trichiura, Ascaris lumbricoides and Taenia spp. were 60.7%, 44.1%, 22.2%, 4.1%, 0.6% and 0.1%, respectively. Heavy intensity infections were 4.2%, 3.6% and 1.8% for O. viverrini, S. mekongi and hookworm, respectively. O. viverrini and S. mekongi infection rates among dogs and cats were 25.0% and 14.7%, respectively. Of the cats tested, 53.1% were infected with O. viverrini. Prevalence of O. viverrini and S. mekongi in snails was 0.3% and 0.01%, respectively. Overall prevalence of O. viverrini infection in fresh water fish was 26.9%, with the highest infection rates occurring in Hampala dispa (87.1%), Cyclocheilichthys apogon (85.7%) and Puntius brevis (40.0%). Illiteracy and lower socioeconomic status increased the risk of O. viverrini infection, while those aged 10-16 years and possessing latrines at home were less likely to be infected. Household dogs and cats that consumed raw fish were significantly and positively associated with O. viverrini infection of the household members. For S. mekongi, children under 9 years old were exposed significantly to this infection, compared to older age groups. Conclusions There is a pressing need to design and implement an integrated helminth control intervention on the Mekong Islands in southern Lao PDR. Given the highly dynamic transmission of O. viverrini, S. mekongi, STH and extended multiparasitism, annual mass-drug administration is warranted along with environmental modifications, health education and improved access to clean water and adequate sanitation to consolidate morbidity control and move towards elimination. Trail registration number Our findings presented here are from a cross-sectional study, therefore, it has not been registered.